Highly flexible mechanical energy harvester based on nylon 11 ferroelectric nanocomposites - Ram, Farsa; Radhakrishnan, Sithara; Ambone, Tushar; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2019)
We report here a flexible piezoelectric energy harvester using castor-oil-derived nylon 11 and biomass-derived cellulose nanocrystals (CNC). Using a simple solution casting process, we were able to fabricate flexible large area nylon 11 and composite films. Neat nylon 11 films crystallized predominantly in the α- phase. Incorporation of CNC at a low concentration of 2–5 wt % resulted in almost complete transition of α-phase to polar γ-phase, which could be attributed to strong hydrogen bonding interactions between CNC and amide groups in nylon 11. This remarkable shift in crystallization behavior also led to enhanced piezoelectric performance. We also found that the addition of 5 wt % glycerol (on the dry weight of nylon 11 or composite) enhanced the flexibility of the film. Energy harvesting devices made from 5 wt % nylon 11/CNC films showed about 2.6 times higher output voltage as compared to neat nylon 11 devices under similar impact conditions, and the effect was durable over 800 cycles. These devices were also used to charge a 10 μF polarized capacitor, and we found that the 5 wt % nylon 11/CNC devices charged up to 3.78 V in 90 s, which is 2.8 times higher than nylon 11 devices. To the best of our knowledge, this is the first report on nylon 11 nanocomposites, where cellulose nanocrystals have been used to enhance the electroactive γ phase in nylon 11 and yield such high piezoelectric performance.

Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric

Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity

Highly moisture-stable ferroelectric ammonium phosphate salt showing piezoelectric energy harvesting and rotation sensing applications - Kushwaha, Vikash; Prajesh, Neetu; Gopal, Animesh; Sahoo, Supriya; Deswal, Swati; Kirana, Antonysylvester; Shanmuganathan, Kadhiravan; Zareba, Jan K.; Boomishankar, Ramamoorthy (Journal of Materials Chemistry A, 2025)
Ferroelectric phosphate-based materials are known for their biocompatibility, dipole switching, and high thermal stability. In this context, we report a novel organic ferroelectric material, diisopropylammonium bis(4-nitrophenyl) phosphate (DIPABNPP), crystallizing in the monoclinic C2 space group. DIPABNPP exhibits a high second harmonic generation (SHG) efficiency 2.5 times higher than that of potassium dihydrogen phosphate (KDP). The ferroelectric nature of DIPABNPP was confirmed by the observation of a rectangular P-E hysteresis loop, which gave a saturated polarization value of 6.82 mu C cm-2. The ferroelectric polar domains of DIPABNPP, along with the bias-dependent amplitude butterfly and phase hysteresis loops, were visualized by piezoresponse force microscopy (PFM). Furthermore, the polydimethyl siloxane (PDMS) composites of DIPABNPP enabled the fabrication of humidity-resistant piezoelectric nanogenerators (PENGs) with energy harvesting and mechanical-electrical sensing capabilities. The top-performing 10 wt% DIPABNPP-PDMS device achieved a peak output voltage of 9.5 V and a charge storage efficiency of 81.8%, successfully powering 53 LEDs. Additionally, its rapid response time of 18.5 ms enables precise rotation sensing capabilities, suggesting potential applications in motion monitoring, such as revolution per minute (RPM) counting. We also present a unique and refined method for obtaining the output work efficiency (OWE) parameter, which quantifies the ratio of harvested electrical energy to the maximum elastic energy stored in the composite device, taking into consideration several key parameters during the PENG measurements. For the 10 wt% DIPABNPP-PDMS composite, an OWE of 13.1% was achieved, highlighting both its current performance and potential for optimization. This metric provides a standardized approach for evaluating PENGs, addressing a critical gap in assessing mechanical-to-electrical energy conversion efficiency.